Interdisciplinary Collaboration: Ethical Issues and Recommendations - Paproski, D. L.; Haverkamp, Beth E. (Canadian Journal of Counselling and Psychotherapy, 2007)
Interdisciplinary collaboration is important, and often vital, to the promotion of client welfare. While counsellors frequently initiate collaboration, they are often faced with unanticipated ethical dilemmas. This article explores some of the issues and ethics of interdisciplinary care, based upon a discussion held among five established and experienced mental health professionals. In an effort to support the collaborative efforts of counsellors and other professionals, they present their perspectives about professional practice and recommendations for effective interdisciplinary work among practitioners.